Oxygenic photosynthetic responses of cyanobacteria exposed under an M-dwarf starlight simulator: Implications for exoplanet’s habitability - Battistuzzi, Mariano; Cocola, Lorenzo; Claudi, Riccardo; Pozzer, Anna Caterina; Segalla, Anna; Simionato, Diana; Morosinotto, Tomas; Poletto, Luca; La Rocca, Nicoletta (Frontiers in Plant Science, 2023)
The search for life on distant exoplanets is expected to rely on atmospheric biosignatures detection, such as oxygen of biological origin. Most of the potentially habitable Earth-like exoplanets have been found orbiting M-dwarf stars. However, these stars are characterized by high light emission in the far-red/near-infrared and a low light emission in the visible, which on Earth sustains oxygenic photosynthesis. So far, it has not been demonstrated how much oxygenic photosynthesis could work under spectral conditions simulating exoplanets orbiting these stars. By utilizing cyanobacteria, the first organisms to evolve oxygenic photosynthesis on our planet, and a starlight simulator capable of reproducing the emission spectrum of an M-dwarf in the range 350–900 nm, we could answer this question. We performed experiments with the cyanobacterium Chlorogloeopsis fritschii PCC6912, capable of Far-Red Light Photoacclimation (FaRLiP), which allows the strain to harvest far-red in addition to visible light for photosynthesis and we compared its responses with a species unable to harvest far-red light, Synechocystis sp PCC6803. We exposed them to three simulated light spectra: M-dwarf, solar and far-red. Then, we analysed growth and photosynthetic acclimation features in terms of pigment composition and photosystem organization. Finally, we determined the oxygen production of the strain directly growing under the different spectra. Both cyanobacteria showed to grow and photosynthesize similarly under M-dwarf and solar light conditions: Synechocystis sp. by utilizing the little light in the visible, C. fritschii by harvesting both visible and far-red light, activating the FaRLiP response. Our experimental results show that an M-dwarf light spectrum could support efficient biological oxygen production, and the data could feed atmospheric models predicting the possibility to have detectable atmospheric biosignatures arising from those exoplanets, if other boundary conditions are met.